P-011 Gastrointestinal Adverse Effects of Immunomodulation: Acute Colitis with Immune Check Point Inhibitor Nivolumab. (March 2016) - Gondal, Bilal; Patel, Parita; Gallan, Alexander; Hart, John; Bissonnette, Marc
Abstract : Background: Recent advances in enhancing anti-tumor activity by immune checkpoint blockade are revolutionizing treatment in cancers especially metastatic melanoma. Nivolumab is a monoclonal antibody that inhibits programmed cell death protein one [PD-1] on T-cells. 1 Certain tumors overexpress PD-1 proteins thereby inactivating T-cell antitumor responses. Nivolumab disrupts this PD-1 receptor pathway, allowing the host immune system to attack the cancer. 2 Although unleashing T-cell immunity has improved prognosis in melanoma, it can also lead to immune mediated toxicity, especially of the gastrointestinal [GI] tract. While many studies have reported GI adverse events with Ipilimumab including colitis and diarrhea, very few cases of Nivolumab-induced colitis have been reported. 1 We report a biopsy confirmed case of PD-1 inhibitor-induced colitis in a 42-year-old woman with advanced metastatic melanoma. Methods: N/A Results: A 42-year-old woman presented with 2 weeks of watery diarrhea, nausea and fevers. Her pertinent past medical history included stage III metastatic melanoma. As part of adjuvant immunotherapy for high-risk patients, she was given Nivolumab. After 3 doses, subsequent Nivolumab treatments were withheld as she developed diarrhea. PCR for Clostridium difficile was also positive at that time. Metronidazole was started for worsening diarrhea. Her symptoms did not improve and she presented to the hospital 10 days later. Her physical exam was unremarkable. WBC was 14.9 and lactate 2.2. Other laboratory studies were normal. Infectious work-up was unrevealing including blood cultures, stool studies, and PCR tests for CMV, HSV and C. difficile. Given the worsening diarrhea and high suspicion for severe Clostridium difficile colitis, she was started on intravenous vancomycin and metronidazole, and the gastroenterology service was consulted. She underwent a colonoscopy, and was found to have an acute left sided colitis with scattered large superficial ulcerations with serpiginous borders. Pathology showed colonic mucosa with patchy crypt dropout and conspicuous apoptotic bodies, consistent with PD-1 inhibitor toxicity. Diagnosis of immune mediated colitis of grade 3/4 was made and patient was started on intravenous steroids. Her diarrhea improved and she was discharged on oral steroids and a tapering dose of vancomycin. She was followed up in oncology clinic a week later. Diarrhea had improved to grade 1 and she was having only 1-2 formed bowel movements per day. Conclusions: The PD-1 inhibitor Nivolumab has proven clinical anti-tumor efficacy and trials overall have established an acceptable safety profile with low rates of colitis and diarrhea. 3 That being said, physicians still need to be watchful for immune-mediated colitis as a possible source of diarrhea in a patient on these inhibitors. Prompt colonoscopic assessment could identify immune colitis early, to allow early discontinuation of the agent and appropriate treatment with steroids, thereby decreasing morbidity and mortality in this high-risk group.